Farmers' awareness and application of banana Xanthomonas wilt control options: The case of Uganda and Kenya - Jogo, W.; Karamura, E.B.; Kubiriba, Jerome; Tinzaara, William; Rietveld, Anne M.; Onyango, M.; Odongo, M. (2011)
Banana is a key staple and cash crop in east and central Africa. However, the recent outbreak of Banana Xanthomonas wilt (BXW) has threatened farmers whose livelihoods depend on the crop. Since 2002, stakeholders embarked on campaigns to sensitize farmers on the disease and its management. This study evaluated the effectiveness of these efforts by examining farmers' awareness of the disease, control options and their application in Uganda and Kenya. Data on BXW distribution and incidence, farmers' awareness of symptoms, mechanisms of spread and control options of the disease and banana production were collected through household surveys conducted in 2010. The results indicated that most farmers (> 90%) were aware of the disease and its symptoms and more than 50% were aware of the recommended control measures. Farmers obtained information on the disease from multiple sources but farmer-to-farmer interaction was the main source suggesting the key role rural social networks play in managing the disease. Not all affected farmers were able to apply control measures due to cost of intervention, lack of labour and inputs. The study recommends strengthening of linkages among stakeholders for better coordination of efforts and participatory development and promotion of farmer-oriented interventions that address farmer constraints.